Transmission of chromosomally integrated human herpesvirus 6 via cord blood transplantation. Issue 1 (25th December 2016) - Yamada, Yuji; Osumi, Tomoo; Imadome, Ken‐Ichi; Takahashi, Etsuko; Ohye, Tamae; Yoshikawa, Tetsushi; Tomizawa, Daisuke; Kato, Motohiro; Matsumoto, Kimikazu
Abstract: Chromosomally integrated human herpesvirus 6 (ciHHV‐6) can be transmitted via allogeneic hematopoietic cell transplantation. To date, only a few cases have been reported. Here, we report a case identified as transmission of ciHHV‐6 via cord blood transplantation. Distinguishing transmission of ciHHV‐6 from HHV‐6 reactivation in cases with high titer of HHV‐6 DNA load after transplantation is important to prevent unnecessary exposure to antiviral drugs that could be toxic.